For what value of m is the equation true? X^2-6x+5=m+(x-3)-6

(1) Answers

1. Simplify brackets x^2-6x+5=m+x-3-6 2. Simplify m+x-3-6 to m+x-9 x^2-6x+5=m+x-9 3. Subtract x from both sides x^2-6x+5-x=m-9 4. Simplify x^2-6x+5-x to x^2-7x+5 x^2-7x+5=m-9 5. Add 9 on both sides x^2-7x+5+9=m 6. Simplify x^2-7x+5+9 to x^2-7x+14 x^2-7x+14=m 7. Switch sides m=x^2-7x+14 You can always check by putting the new value of m into the equation (I already did that, so you don´t have to) 1.2. Simplify brackets x^2-6x+5=x^2-7x+14+3-3-6 2.2. Cancel x^2 on both sides -6x+5=-7x+14-x-3-6 3.2. Simplify -7x+14+x-3-6 to -6x+14-3-6 -6x+5=-6x+14-3-6 4.2. Simplify -6x+14-3-6 to -6x+5 -6x+5=-6x+5 5.2 Since both sides are equal, the value for m is x^2-7x+14 Have a nice day :D

Add answer